Case Report: Whole Exome Sequencing Revealed Two Novel Mutations of PIEZO1 Implicated in Nonimmune Hydrops Fetalis - Chen, Yuan; Jiang, Ying; Chen, Bangwu; Qian, Yeqing; Liu, Jiao; Yang, Mengmeng; Zhao, Baihui; Luo, Qiong (Frontiers in Genetics, 2021)
Nonimmune hydrops fetalis (NIHF) is a serious and complex fetal condition. Prenatal diagnosis of hydrops fetalis is not difficult by ultrasound. However, determining the underlying etiology of NIHF remains a challenge which is essential to address for prenatal counseling. We extracted DNA from a proband prenatally diagnosed unexplained NIHF. Trio-whole exome sequencing (WES) was performed to filter candidate causative variants. Two gene mutations were identified as a compound heterozygous state in the proband. Both variants located on the PIEZO1 gene: c.3895C > T, a missense mutation in exon 27 paternally inherited; c.4030_4032del, a maternally inherited in-frame deletion in exon 28. Both variants were first reported to be related to NIHF. PIEZO1 gene mutations, leading to an autosomal recessive congenital lymphatic dysplasia, which can present as NIHF and partial or complete resolution postnatally. In conclusion, WES can aid in the elucidation of the genetic cause of NIHF and has a positive effect on the assessment of prognosis.